Potensi Limbah Cair Tahu sebagai Pupuk Organik Cair di RT. 31 Kelurahan Lempake Kota Samarinda - Rahma Nur Amalia; Shalaho Dina Devy; Angga Syfa Kurniawan; Nur Hasanah; Elisa Destephani Salsabila; Dira Anis Ageung Ratnawati; Febry Muhammad Fadil; Nur Aqsan Syarif; Guntur Arsi Aturdin (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2022)
Making tofu produces a large volume of waste, especially the liquid waste. This tofu liquid waste contains high protein which is easily decomposed quickly. If this liquid is discharged into the environment without prior treatment, it can cause a foul odor and an unpleasant atmosphere. Therefore, the purpose of this service activity is to process tofu liquid waste into organic fertilizer by fermentation. The fermentation process takes 15 days with the addition of EM4, brown sugar solution, and enough water. All ingredients are mixed and stirred evenly then put in a closed container. After about two weeks, the liquid organic fertilizer can be used for fertilizing plants by the community on Jalan Rejo Mulyo, RT. 31, Lempake Village, North Samarinda District. This activity involved 8 students of Mulawarman University Thematic Community Service Program. The form of activity carried out are directly visit the location to obtain data through interviews and observations, data processing, and making conclusion for devotion activities.